2004
DOI: 10.1111/j.0105-2896.2004.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in T‐helper 1 development – resolved and unresolved

Abstract: T-helper 1 cell (Th1) development participates in immunity to many pathogens in part by providing a source of interferon (IFN)-gamma that contributes numerous protective effects. The process of Th1 development involves signals provided by antigen-presenting cells and cytokines produced in response to pathogens, with IFN-gamma itself, interleukin (IL)-12, and IL-18 each promoting the process in some way. Despite the rapid progress into mechanisms of Th1 development in recent years, there are still a number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 95 publications
0
60
1
Order By: Relevance
“…Type 1 immune responses and the effector protein IFN-␥ play a critical role in the control of the inflammatory process, the protection against pathogens and tumors (4,5). In this study, we demonstrated that CD47 negatively regulated type 1 humoral and cellular immune responses in vivo.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Type 1 immune responses and the effector protein IFN-␥ play a critical role in the control of the inflammatory process, the protection against pathogens and tumors (4,5). In this study, we demonstrated that CD47 negatively regulated type 1 humoral and cellular immune responses in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…Nonetheless, IFN-␥ plays a critical role in the protective response against intracellular pathogens that include parasites, mycobacteria, Salmonella, and Listeria (5,10,61). Whether CD47 decreases pathogen-driven Th1 responses remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has become clear that IL-12 and IL-18 can also activate T cells in an antigenindependent fashion. 60 Studies of IFN-␥ production by murine CD4 ϩ T cells have characterized separate IL-12/IL-18 and T-cell receptor signaling pathways. 61 Interactions between innate and adaptive stimuli for cytokine responses by murine CD8 ϩ T cells have been investigated in a viral infection model in which both IL-12/IL-18 and antigen result in IFN-␥ production, but only T-cell receptor signaling induces IL-2 secretion, which is pivotal for T-cell clonal expansion.…”
Section: Ccr7mentioning
confidence: 99%
“…In contrast, STAT-4 was exclusively activated by R5 gp120. STAT-4 is a member of the STAT family of transcription factors and plays a central role in the polarization of T lymphocytes toward a Th1 phenotype (32). (13,14).…”
Section: Figmentioning
confidence: 99%